Parents using live streaming video cameras to view infants in a regional NICU: Impacts upon bonding, anxiety and stress. Issue 1 (February 2022) - Kilcullen, Meegan Lesley; Kandasamy, Yogavijayan; Evans, Michelle; Kanagasignam, Yogesan; Atkinson, Ian; van der Valk, Steven; Vignarajan, Janardhan; Baxter, Michelle
Abstract: Background: While live streaming from the NICU has entered standard care in some tertiary hospitals, few studies have been explored the impact of this technology upon parents. Aim: To understand the impact of live-streaming vision of infants in NICU to their parents. Method: In the present study, cameras were installed and parents live-streamed vision of their infants while admitted to a regional NICU. Camera usage data were recorded, and parent-infant bonding, parental stress and anxiety data were collected via online survey across four time points. Results: While parents preferred to be with their infant in person, there was strong acceptance of the technology. There were no significant differences in camera usage across the admission and at 3-month follow-up. The relationships between camera usage and bonding, stress, and anxiety scores varied across time points and no significant changes in anxiety, stress and bonding scores were identified. Conclusion: Implementation of this technology into standard care requires streaming stability and support for staff and parents to effectively use the technology.